2009
DOI: 10.1152/ajpregu.91030.2008
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex sensitivity varies during the rat estrous cycle: role of gonadal steroids

Abstract: -Baroreflex sensitivity (BRS) increases in women during the luteal phase of the menstrual cycle, when gonadal hormones are elevated, but whether a similar cycle-dependent variation in BRS occurs in rats is unknown. In addition, whether cyclic BRS changes depend on gonadal steroids has not been previously investigated. To test these hypotheses, BRS was determined in cycling female rats using two approaches: 1) baroreflex control of renal sympathetic nerve activity (RSNA) in anesthetized rats; 2) cardiovagal spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
59
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 61 publications
11
59
0
1
Order By: Relevance
“…Despite animal work supporting a hormonal effect on baroreceptor sensitivity (13,17,29,(32)(33)(34), our finding of no change in baroreflex control of SNA with hormonal phase in non-OCP uses is consistent with prior reports in humans (4,12). In these earlier reports, the sympathetic baroreflex sensitivity is assessed by the nonpharmacological approach in which Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite animal work supporting a hormonal effect on baroreceptor sensitivity (13,17,29,(32)(33)(34), our finding of no change in baroreflex control of SNA with hormonal phase in non-OCP uses is consistent with prior reports in humans (4,12). In these earlier reports, the sympathetic baroreflex sensitivity is assessed by the nonpharmacological approach in which Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Although estrogen is thought to exert a sympathoinhibitory effect (13,17,24,25,29,38), whereas progesterones may increase resting SNA in humans (6,10), the net effect may depend on the relative level, source (endogenous or exogenous), and bioactivity of each hormone. OCPs contain pharmacological doses of estrogen and progesterone, providing severalfold greater hormonal levels and activity in the plasma and central nervous system compared with endogenous hormones and are metabolized into compounds that are also bioactive.…”
Section: Discussionmentioning
confidence: 99%
“…The sex steroid hormones are required for changes in baroreflex sensitivity, as shown by the changes that occur in the cardiovagal baroreflex sensitivity and renal sympathetic nerve activity during the estrous cycle of female rats that are abolished by OVX (25). Additionally, several studies have demonstrated the modulation of hypotensive responses by estrogen, although the data are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in conscious ovary-intact female rats the arterial baroreflex control of renal SNA varies across the estrous cycle, suggesting an effect of differing levels of circulating ovarian hormones (18). However, contradictions exist regarding the effects of sex and ovarian hormones on the arterial baroreflex regulation; for example, although previous work has demonstrated that the arterial baroreflex regulation of renal SNA varies across the estrous cycle (3,18), both previous (24,47) and the present evidence have shown that ovariectomy does not alter arterial baroreflex control of renal SNA. Given the potential importance of the arterial baroreflex in mediating changes in SNA in heart failure, future work investigating the mechanistic role of sex and ovarian hormones in mediating the arterial baroreflex is required.…”
Section: R174 Ovarian Hormones Preserve Arterial Baroreflex Following MImentioning
confidence: 99%
“…Sex differences in arterial baroreflex regulation of SNA do exist, with healthy female rats demonstrating a reduced ability of the arterial baroreflex to increase SNA in animals (47,15), a finding confirmed in humans using muscle SNA recordings (52). Furthermore, varying levels of ovarian hormones in females during the reproductive cycle or following menopause can significantly alter arterial baroreflex regulation of SNA (16,18,37,52). It is possible that sex and sex hormone status may contribute to inconsistent findings regarding the arterial baroreflex regulation in heart failure.…”
mentioning
confidence: 95%